Organizational Silence and Positive Leadership Strategies: The Mediating Role of Psychological Empowerment - Iraj Mehdizadeh; Saeed Rajaeepor; Seyed Ali Siadat (مدیریت دولتی, 2023)
Objective Organizational silence is a prevalent occurrence within companies, which can lead to serious adverse outcomes. Consequently, managers and researchers studying organizational behavior recognize it as a noteworthy challenge faced by organizations. The primary goal of this study was to predict and clarify the phenomenon of organizational silence by implementing positive leadership strategies and investigating the potential mediating effect of psychological empowerment. Methods For practical and managerial purposes, this study employed a combination of developmental instruments and phenomenology based on lived experiences in order to identify the sub-constructs of organizational silence. Additionally, a descriptive correlational design was utilized to investigate the relationship between variables. The statistical population consisted of all staff and faculty members at Farhangian University in the 9th district of Eastern Iran. Qualitative data were collected through semi-structured interviews with 26 participants selected up to theoretical saturation. Data were then categorized through theme analysis in four dimensions (context, causal, process, and intervention) and 10 components, including socio-communication, economic, organizational, political, cultural, informational, regulatory, managerial, human, and human resources. A 65-question questionnaire was developed based on these themes. In the quantitative part of the study, 180 people were selected using stratified random sampling according to Cochran's formula. The Kaiser, Meyer, and Olkin (KMO) index was used to investigate the adequacy of the sample, and the index for all data was over 0.6, indicating the adequacy of the sample data for factor analysis. The study utilized Cameron's Positive Leadership Questionnaire (2008), Spritzer and Mishra's Psychological Empowerment Questionnaire (1997), and a researcher-made Organizational Silence Questionnaire. The reliability of the instruments in terms of Cronbach's alpha was 0.94, 0.77, and 0.93, respectively. The convergent validity of the questionnaires was 0.86, 0.50, and 0.62, respectively. The data were analyzed using SPSS 24 and Smart PLS software. Results The study investigated the model from two criteria, R2 and Q2 values, and the overall model of structural equations was evaluated using the "goodness of fit" criterion. The goodness of fit value was 0.324, and considering the three values of 0.01, 0.25, and 0.36, the appropriate fit of the overall research model was confirmed. The results showed a negative and significant relationship between positive leadership strategies (positive communication, positive human relationships, positive significance, and positive atmosphere) and psychological empowerment (meaningfulness, competence, self-determination, effectiveness, and trust) with organizational silence. Additionally, psychological empowerment plays a mediating role between positive leadership and organizational silence. Conclusion The study concludes that utilizing positive leadership styles and employee empowerment can effectively reduce employees' silence. Therefore, it is recommended that administrators at Farhangian University establish an environment that fosters employee growth and well-being. Managers can facilitate empowerment among their employees by taking into account their psychological needs, fostering trust and involvement, and delegating authority to grant independence and self-determination. Additionally, managers can provide positive and constructive feedback, establish positive relationships, and create a positive atmosphere to create a safe and comfortable environment for employees to comment more easily. At the organizational level, employees should have access to professional development programs. In general, dedicating resources to the enhancement and cultivation of positive leadership and employee empowerment can enhance the growth and efficiency of the organization through increased employee engagement and collaboration.